Early patterning followed by tissue growth establishes distal identity in Drosophila Malpighian tubules - Beaven, Robin; Denholm, Barry (Frontiers in Cell and Developmental Biology, 2022)
Specification and elaboration of proximo-distal (P-D) axes for structures or tissues within a body occurs secondarily from that of the main axes of the body. Our understanding of the mechanism(s) that pattern P-D axes is limited to a few examples such as vertebrate and invertebrate limbs. Drosophila Malpighian/renal tubules (MpTs) are simple epithelial tubules, with a defined P-D axis. How this axis is patterned is not known, and provides an ideal context to understand patterning mechanisms of a secondary axis. Furthermore, epithelial tubules are widespread, and their patterning is not well understood. Here, we describe the mechanism that establishes distal tubule and show this is a radically different mechanism to that patterning the proximal MpT. The distal domain is patterned in two steps: distal identity is specified in a small group of cells very early in MpT development through Wingless/Wnt signalling. Subsequently, this population is expanded by proliferation to generate the distal MpT domain. This mechanism enables distal identity to be established in the tubule in a domain of cells much greater than the effective range of Wingless.